Magnetic silver hybrid nanoparticles for surface-enhanced resonance Raman spectroscopic detection and decontamination of small toxic molecules - Han, Xiao Xia; Schmidt, Annette M.; Marten, Gernot; Fischer, Anna; Weidinger, Inez M.; Hildebrandt, Peter (ACS nano, 2013)
Magnetic hybrid assemblies of Ag and Fe3O4 nanoparticles with biocompatibly immobilized myoglobin (Mb) were designed to detect and capture toxic targets (NO2-, CN-, and H2O2). Mb was covalently attached to chitosan-coated magnetic silver hybrid nanoparticles (M-Ag-C) via glutaraldehyde that serves as a linker for the amine groups of Mb and chitosan. As verified by surface-enhanced resonance Raman (SERR) spectroscopy, this immobilization strategy preserves the native structure of the bound Mb as well as the binding affinity for small molecules. On the basis of characteristic spectral markers, binding of NO2-, CN-, and H2O 2 could be monitored and quantified, demonstrating the high sensitivity of this approach with detection limits of 1 nM for nitrite, 0.2 μM for cyanide, and 10 nM for H2O2. Owing to the magnetic properties, these particles were collected by an external magnet to achieve an efficient decontamination of the solutions as demonstrated by SERR spectroscopy. Thus, the present approach combines the highly sensitive analytical potential of SERR spectroscopy with an easy approach for decontamination of aqueous solutions with potential applications in food and in environmental and medical safety control. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: decontamination; magnetic nanoparticles; myoglobin; SERR; silver nanoparticles; spectroscopic detection; toxic small molecule